Crocetin: A Systematic Review - Guo, Zi-Liang; Li, Mao-Xing; Li, Xiao-Lin; Wang, Peng; Wang, Wei-Gang; Du, Wei-Ze; Yang, Zhi-Qiang; Chen, Sheng-Fu; Wu, Di; Tian, Xiu-Yu (Frontiers in Pharmacology, 2022)
Crocetin is an aglycone of crocin naturally occurring in saffron and produced in biological systems by hydrolysis of crocin as a bioactive metabolite. It is known to exist in several medicinal plants, the desiccative ripe fruit of the cape jasmine belonging to the Rubiaceae family, and stigmas of the saffron plant of the Iridaceae family. According to modern pharmacological investigations, crocetin possesses cardioprotective, hepatoprotective, neuroprotective, antidepressant, antiviral, anticancer, atherosclerotic, antidiabetic, and memory-enhancing properties. Although poor bioavailability hinders therapeutic applications, derivatization and formulation preparation technologies have broadened the application prospects for crocetin. To promote the research and development of crocetin, we summarized the distribution, preparation and production, total synthesis and derivatization technology, pharmacological activity, pharmacokinetics, drug safety, drug formulations, and preparation of crocetin.